Determination of the Psychometric Properties of the Inventory of Drug Use Consequences (INDUC) and Its Relationship with General Health (GHQ-28) in an Iranian Population - Tarzi, Fatemeh; Younisi Broujeni, Jalil; Fathi, Ali (KMAN Counseling & Psychology Nexus, 2026)
The purpose of the present study was to examine the psychometric properties of the Inventory of Drug Use Consequences. This study was an exploratory investigation based on classical test theory and is classified as an instrument development study. The statistical population consisted of all individuals with a history of substance use who were receiving treatment at Karizak Addiction Treatment Center. A convenience sample of 382 participants was selected from this center. The Inventory of Drug Use Consequences (INDUC) is a standardized instrument for assessing the negative consequences of substance use, developed by Tonigan and Miller (2022). In this field study, data were collected using the INDUC and the General Health Questionnaire (GHQ-28). Data were gathered through the Inventory of Drug Use Consequences (Tonigan & Miller, 2022) and the General Health Questionnaire (Goldberg, 1972) and analyzed using exploratory factor analysis (principal component analysis) and confirmatory factor analysis with SPSS and AMOS software. Based on the findings of this study, the Inventory of Drug Use Consequences demonstrated satisfactory psychometric properties and reliability in the Iranian population. Reliability and validity at both the subscale and total score levels, along with good model fit of the five-factor structure in both exploratory and confirmatory analyses, indicate the adequacy of the factor structure of this instrument. The results showed that the items of the Inventory of Drug Use Consequences possess acceptable reliability and adequate construct validity. Moreover, significant correlations were observed between the total scores and subscales of the Inventory of Drug Use Consequences and the General Health Questionnaire.